The Influence of Learning Motivation, Family Environment, and Discipline on Student Learning Outcomes - Umara, Yunita; Rizki , Ilham; Zaydan, Sadid; Rifansyah, Muhammad Rio; Cahaya, Natasya Putri (General Multidisciplinary Research Journal, 2026)
Introduction: Improving student learning outcomes is a strategic issue in national education development due to fluctuating literacy and numeracy achievements and differences in academic performance among students. Learning outcomes are influenced by various internal and external factors. Learning motivation, as an internal factor, plays a crucial role in encouraging students' active involvement in the learning process, while learning discipline, as a behavioral factor, determines students' consistency and effectiveness in managing learning activities. On the other hand, the family environment, as an external factor, contributes through emotional support, learning facilities, and parenting styles. Methods: This study used a quantitative approach with a survey design. Data were collected through standardized questionnaires to measure learning motivation, family environment, and discipline, as well as documentation of students' academic grades. Data analysis was performed using multiple linear regression with the classical assumption test, t-test, F-test, and coefficient of determination. Results: The results showed that all three variables simultaneously had a positive and significant effect on learning outcomes. Partially, learning motivation and discipline had a significant effect, while the family environment showed a positive effect with moderate significance. Conclusion and Suggestion: This study emphasizes the importance of strengthening student learning motivation and discipline, supported by the role of the family. It is recommended that there be synergy between schools and parents and the development of further research with broader variables and approaches.